Identification of the Different Gene Expression Characteristics from Liver Cirrhosis to Hepatocellular Carcinoma Using Single-Cell Sequencing Analyses - Xin Xing; Jian Song (Journal of Immunology Research)
The occurrence of hepatocellular carcinoma (HCC) is closely related to the chronic inflammation which caused liver fibrosis and cirrhosis, and the interaction between HCC and its microenvironment further drives tumorigenesis. However, the single-cell resolution in vivo study is lacking, which limits our molecular understanding of tumour biology in the liver. Here, using published single-cell sequencing technology (scRNA-seq) database, we analyzed the liver microenvironment at high resolution in an unbiased manner and demonstrated the transcriptomic comparison between various cell populations and subpopulations in HCC and cirrhosis tissues. We found that eight genes that are specifically expressed in the endothelial cell and stellate cell of the HCC patients and correlated them with their survival rate, which may provide novel diagnosis and treatment targets for the clinical application.